High sensitivity troponin and COVID-19 outcomes. Issue 1 (2nd January 2022) - Papageorgiou, Nikolaos; Sohrabi, Catrin; Prieto Merino, David; Tyrlis, Angelos; Atieh, Abed Elfattah; Saberwal, Bunny; Lim, Wei-Yao; Creta, Antonio; Khanji, Mohammed; Rusinova, Reni; Chooneea, Bashistraj; Khiani, Raj; et al.
Abstract: Background: Recent reports have demonstrated high troponin levels in patients affected with COVID-19. In the present study, we aimed to determine the association between admission and peak troponin levels and COVID-19 outcomes. Methods: This was an observational multi-ethnic multi-centre study in a UK cohort of 434 patients admitted and diagnosed COVID-19 positive, across six hospitals in London, UK during the second half of March 2020. Results: Myocardial injury, defined as positive troponin during admission was observed in 288 (66.4%) patients. Age (OR: 1.68 [1.49–1.88], p  < .001), hypertension (OR: 1.81 [1.10–2.99], p  = .020) and moderate chronic kidney disease (OR: 9.12 [95% CI: 4.24–19.64], p  < .001) independently predicted myocardial injury. After adjustment, patients with positive peak troponin were more likely to need non-invasive and mechanical ventilation (OR: 2.40 [95% CI: 1.27–4.56], p  = .007, and OR: 6.81 [95% CI: 3.40–13.62], p  < .001, respectively) and urgent renal replacement therapy (OR: 4.14 [95% CI: 1.34–12.78], p  = .013). With regards to events, and after adjustment, positive peak troponin levels were independently associated with acute kidney injury (OR: 6.76 [95% CI: 3.40–13.47], p  < .001), venous thromboembolism (OR: 11.99 [95% CI: 3.20–44.88], p  < .001), development of atrial fibrillation (OR: 10.66 [95% CI: 1.33–85.32], p  = .026) and death during admission (OR: 2.40 [95% CI: 1.34–4.29], p  = .003). Similar associations were observed for admission troponin. In addition, median length of stay in days was shorter for patients with negative troponin levels: 8 (5–13) negative, 14 (7–23) low-positive levels and 16 (10–23) high-positive ( p  < .001). Conclusions: Admission and peak troponin appear to be predictors for cardiovascular and non-cardiovascular events and outcomes in COVID-19 patients, and their utilisation may have an impact on patient management.